DETERMINANTS OF COMMUNAL FARMERS’ WILLINGNESS TO PAY FOR HUMAN-WILDLIFE CONFLICT MANAGEMENT IN THE PERIPHERY OF SAVE VALLEY CONSERVANCY, SOUTH EASTERN ZIMBABWE - P. Mhuriro-Mashapa; E. Mwakiwa; C. Mashapa (Journal of Animal and Plant Sciences, 2017)
Human-wildlife conflicts are a concern in communal areas adjacent to protected areas in Zimbabwe. The objectives of the present study were to (i) investigate the determinants of farmers’ willingness to pay for human-wildlife conflict management and (ii) estimate the opportunity cost of human-wildlife conflict management in the periphery of Save Valley Conservancy, south eastern Zimbabwe. Interviews with individual household heads, key informants and focus group discussions were done. A stratified random sampling technique basing on distance from Save Valley Conservancy was used in selecting the households for data collection. Data collection was done in July 2015, using semi-structured questionnaires administered to a stratified and randomly selected 300 households and 20 key informants. Elephants, buffaloes, hyenas and lions were most problem wild animals in the study area. The following factors were significant in explaining the household’s willingness to pay for human-wildlife conflict management, namely, education level of household head (p = 0.006), household income (p = 0.001), distance from Save Valley Conservancy boundary (p = 0.036) and awareness of human-wildlife management. Despite the absence of an active formal agricultural insurance institution, farmers were willing to pay about USD157.67 annually per household, for human-wildlife conflict management in the study area.
Keywords: communal areas; crop raids; livestock predation; livelihood; Save Conservancy; wild animals